Pengaruh Penggenangan dan Pengeringan terhadap Populasi dan Siklus Hidup Nematoda Puru Akar Padi (Meloidogyne graminicola) - Mulyadi Mulyadi; B. Triman (Universitas Gadjah Mada, 1997)
The objectIves of the research were to study the effect of flooding and draining on the population and life cycle of root-knot nematode of rice (Meloidogyne graminicola). To study the effect of flooding and draining on the population of M. graminicola two experiments were done within two period of planting of rice IR 64. These experiments were arranged in completely randomize design with four replications. For studying the effect of flooding and draining on the life cycle of M. graminicola, the experiment was done within 30 days. The research results showed: 1) continuously flooding inhibit the penetration and population development of M. graminicola on rice IR 64, but the life cycle of M. graminicola was not affected; and 2) seventy two hours period of draining enhanced the development of M. graminicola compared to period of draining shorter than 72 hours.